Phytochemical evaluation and in vitro antioxidant potential of Cycas circinalis L. - Kazi, Zoofishan; Singh, Simran; Lobo, Vijaya (Current Botany, 2025)
Cycas circinalis L., a gymnosperm, is traditionally used by tribal people for various medicinal and culinary purposes. This study investigates the phytoconstituents and antioxidant potential of the leaves, bark, and male cone of C. circinalis. Qualitative screening and quantitative analysis were conducted, followed by analysis of antioxidant potential using in vitro assays. High-performance thin-layer chromatography (HPTLC) analysis of phenols and flavonoids was carried out to identify active constituents. Various phytoconstituents, including alkaloids, phenols, flavonoids, glycosides, quinones, and sterols, were identified in different extracts. The ethanolic extract of the leaves exhibited the highest total phenolic content (8.169 mg GAE/g), while the male cones showed the highest flavonoid content (2.825 mg QE/g). The bark demonstrated significant radical scavenging activity, particularly in ABTS (IC50 59.44 μg/mL) and DPPH (IC50 358.3 μg/mL) assays. In contrast, the leaves exhibited moderate activity across all assays, and the male cones showed relatively lower antioxidant activity, except in the total antioxidant capacity assay (19.25 mg AAE/g). HPTLC analysis detected gallic acid in the bark, along with several unidentified bands. This study is the first to report presence of gallic acid in the extract of bark of C. circinalis. Given the plant’s traditional use in treating swellings, wounds, and ulcers, along with the presence of diverse secondary metabolites and significant in vitro bioactivity, this study highlights the potential of C. circinalis as a natural antioxidant with promising applications in wound treatment.